Strain Profiling of a Ferritic‐Martensitic Stainless Steel Sheet — Comparing Synchrotron with Conventional X‐Ray Diffraction. (28th December 2014) - Olsson, C.‐O. A.; Boström, M.; Buslaps, T.; Steuwer, A.
Abstract To improve the fatigue resistance of stainless steel sheet, it is a common practice to induce compressive residual stress in the surface through shot‐peening or tumbling. Stress depth profiles obtained by tumbling of thin stainless steel tensile rods were analysed using laboratory and synchrotron X‐Ray Diffraction (XRD). Both the non‐destructive synchrotron and the laboratory XRD etch‐depth profile gave similar results: a residual stress profile decaying over a depth not exceeding 50 µm into the material.